Self-monitoring of blood glucose in type 2 diabetes: steps toward consensus - Davis, T. M. E. (2008)
Those involved in type 2 diabetes care must be puzzled by the lack of consensus on self-monitoring of blood glucose (SMBG) (1,2,3), especially in non–insulin-treated patients. This is reflected by wide between-country variation in reimbursement for glucose meters and strips. Balanced evaluation of available data is required; however, further trials are needed to provide robust evidence as to how and in which groups SMBG use is justified.